Analisis Crashing Pelaksanaan Pekerjaan Berulang pada Proyek Perumahan dengan Metode LoB (Line of Balance) Studi Kasus Perumahan Bumi Podo Rukun - Fadjarwati, Indah; Oetomo, Wateno; Widhiarto, Herry (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2025)
Housing construction is a recurring and sustainable job. So if the scheduling does not take into account the character of this work then the repetitive work unit will experience a delay (lag). So that it will result in the duration of the project. To overcome this, an uninterrupted scheduling method is needed from one unit to the next. The scheduling method that matches this type of repetitive work is the Line of Balance (LoB) because each activity / activity is described in a straight line and the speed of work can be changed according to needs. This is to avoid the occurrence of crashes / conflicts between activities. This method can also minimize the delay time as mentioned above. But this method cannot show dependency between critical activities and the other activities. For this reason, another method is needed in order to fill this gap. The suitable method is CPM through Microsoft Project. This combination of methods besides managing the time of project implementation also regulates human resources, namely by maximizing the allocation of human resources. Because in this multi-unit project the quantity of work is the main thing. From some analysis calculations, the results obtained that the addition of buffers with productivity speed smoothing, and the acceleration of the duration of the activity more effective to accelerate the implementation time of the project with a duration of 154 days.